Knowledge of contraception among high school and university students in West Pomerania voivodeship - Świderska, Janina; Dubiel, Paulina; Czekawy, Izabela; Gorzko, Amalia; Chaszczowska, Anna; Skibko, Radosław; Krejczy, Kamila; Torbé, Dorota; Czmbaluk-Płoska, Aneta; Chuecka- Głaz, Anita; et al. (Journal of Education, Health and Sport, 2018)
Adolescents and young adults are the most vulnerable group of unplanned pregnancy, which may result in early motherhood or often unsafe, illegal abortion. The teenager birth rate in Poland (total number of live births per 1000) is one of the highest in European Union and the West Pomerania voivodeship has the highest teenager birth rate in Poland. Low level of contraceptive use, choosing low efficacy methods and errors resulting from inadequate knowledge are considered the main reasons of unplanned pregnancies. In this study we aimed to assess the knowledge of high school and academic students of the West Pomeranian vivodeship about contraception. We recruited 500 students who were asked to fill in an anonymous questionnaire checking knowledge, beliefs and experiences regarding the use of contraception. 277 of the participants were using contraceptive methods. Our results showed that the knowledge about pregnancy prevention is insufficient and young people choose methods that are ineffective. The feeling of shame and the need to visit a doctor and undergo a gynecological examination to get a prescription are thought to be the main limitation in accessibility to contraceptive methods in the studied group. Since most of the respondents indicate the internet as the main source of their knowledge, it seems reasonable to create a professional website addressed to teenagers and young adults, introducing the subject of contraception.